Nutrition and hydration for handball - Molina-López, J.; Planells, E. (Handball Sports Medicine, 2018)
Handball players face a variety of nutritional challenges during the competitive season. Although there has been an increase in nutrition research and exercise over the last decade, nutrition remains a largely unknown area in sports such as handball. There is little information on the nutritional habits of handball players at any level of the game. This updated document performs a rigorous, systematic, and evidence-based analysis of nutrition and specific literature with current scientific data related to energy needs, nutrient requirements, and hydration during training as well as competition on athletes in team sports, particularly among handball players. Energy and macronutrient needs, especially carbohydrates and proteins, must be met during periods of high physical activity to maintain body weight, replenish glycogen stores, and provide adequate protein to build and repair tissue. Fat intake should be sufficient to supply essential fatty acids and fat-soluble vitamins and to contribute energy for weight maintenance. Micronutrients play an important role in energy production, hemoglobin synthesis, and the maintenance of bone health, adequate immune function, and protecting the body against oxidative damage. Due to the absence of specific micronutrient recommendations in team sports like handball, the consumption of unbalanced diets with low micronutrient density may be insufficient to cover the players` increased needs. Athletes should be well hydrated before exercise and drink enough liquids during and after exercise to balance fluid loss. Sports drinks containing carbohydrates and electrolytes can be consumed before, during, and after exercise to help maintain blood glucose concentration, provide fuel for muscles, and decrease the risk of dehydration and hyponatremia.